Mutual funds in Greece: case study of domestic equity mutual funds during a financial crisis. Issue 7 (10th July 2017) - Koutsokostas, Drosos; Papathanasiou, Spyros
Abstract : Purpose: The purpose of this paper is to examine the performance of Greek equity mutual funds for the period 2012-2016, analyzing further the selectivity and market timing ability, and short-term performance persistence for the period 2015-2016. Design/methodology/approach: Utilizing a survivorship-bias-controlled sample of 25 funds and daily data, the authors use single-index (Jensen, 1968) and multi-factor (Carhart, 1997) models to evaluate risk-adjusted returns using the General Index of Athens Stock Exchange as a benchmark. The Treynor-Mazuy (1966) and Henriksson-Merton (1981) models are used to assess the stock selection and market timing abilities of fund managers. In order to investigate short-term performance persistence, the authors implement a variety of parametric (Bollen and Busse, 2005) and nonparametric tests (Malkiel, 1995; Brown and Goetzmann, 1995; Kahn and Rudd, 1995). Findings: Results show that the funds underperformed the General Index, mainly due to the managers' market timing inability. Furthermore, weak evidence for short-term performance persistence has been documented. Research limitations/implications: Checking for performance persistence, it was impossible to rank funds and form deciles according to their estimated abnormal returns, as in Bollen and Busse (2005), due to the small number of mutual funds operating in Greece. Originality/value: Empirical studies regarding the performance of Greek equity mutual funds are still limited. Therefore, this paper intends to fill this gap by providing further evidence of performance evaluation.